Implementasi Pendekatan Open Ended dan Pengaruhnya terhadap Kemampuan Berpikir Kritis Matematis Siswa - Saryantono, Buang; Noviyana, Hesti; Pratama, Elvandri Yogi (Lentera: Jurnal Ilmiah Kependidikan, 2022)
Society 5.0 requires the ability to think critically to deal with various changes. The ability to think critically in an era that emphasizes the role of humans as the center of civilization through the use of digital technology is not in line with the fact that the ability to think critically in class VIII odd semester students at SMP Negeri 26 Bandar Lampung in the 2022/2023 academic year. The ability to think critically mathematically in class VIII students is still a problem, for this reason this study aims to determine the effect of implementing the Open Ended approach on students' critical thinking ability in mathematics. This quasi-experimental study, with a population of all VIII grade students, totaling 227 students, while the samples were VIII E class as the experimental class and VIII G class as the control class. Samples were taken using the Cluster Random Sampling technique and to determine students' mathematical critical thinking skills were given a test in the form of a description of 5 questions which had previously been tested for validity and reliability. From the results of testing the hypothesis using the t test, the value of thitung = 3.35 is obtained. From the t distribution table at a significant level of 5% it is known that tdaftar = t(1-α) = 1.67. Thus thitung > tdaftar, so it can be concluded that the implementation of the Open Ended approach can affect the mathematical critical thinking skills of Grade VIII students in odd semesters at SMP Negeri 26 Bandar Lampung in the 2022/2023 academic year.